Grieving processes, ubuntu values, and challenges encountered by families that experienced losses due to the COVID-19 pandemic in Vhembe District, Limpopo Province - Mudau, Dzivhuluwani Rinah (My University, 2025)
Engaging in Ubuntu with grieving individuals is considered a component of the healing process, in African cultures. Grieving, however, had to be altered in shape and form due to the Coronavirus pandemic of 2019 (COVID-19), as numerous restrictions had to be implemented, worldwide, to mitigate the spread of the lethal virus. This research employed a qualitative methodology for data collection and analysis, utilising in-depth interviews. This study employed a single data collection instrument, interviews, to collect data from 20 participants across 10 families. Participants were picked conveniently by purposive sampling procedures. The data underwent thematic analysis, and the findings were presented thematically, with analogous perspectives and experiences consolidated. Data was collected and handled in a manner to ensure the privacy and confidentiality of the participants details were not compromised. The recommendations from this study were derived from the analyses and interpretations of the findings. The results indicated that during the COVID-19 pandemic, bereaved families encountered emotional, social, and cultural obstacles, such as isolation, interrupted rituals, and insufficient community assistance, which exacerbated their mourning. Nonetheless, Ubuntu principles, such as empathy, solidarity, and collective resilience facilitated families' adaptation to evolving circumstances and recovery. The research advocates for interventions, such as culturally-attuned mental health therapies, utilising internet platforms to preserve social connections during disasters, and communities formulating recommendations to assist bereaved families during public health emergencies. Ethical principles such as, informed consent were adhered to, and the privacy and anonymity of participants were maintained throughout the research procedure.
M. A. in Psychology
Department of Psychology
Keywords: COVID-19; UCTD; Grieving; Lockdown; Mourning; Bereavement; Coping Mechanism; Ubuntu